Model Perencanaan Infrastruktur Desa dalam Perspektif Pembangunan Berkelanjutan - Yuli Dwi Yusrani Anugrah; Sa’adatu Mukarromatil Arifah; Taufiqur Rohman (Idarotuna : Journal of Administrative Science, 2025)
Effective village infrastructure planning requires a model that balances technical aspects with active community participation, a core principle of sustainable development. This research critically examines the infrastructure planning process in Wates Kulon Village, Ranuyoso District, Lumajang Regency, through the lens of sustainable development. While the formal procedure for formulating the Medium-Term Village Development Plan (RPJMDes) adheres to the national regulation (Permendagri No. 114/2014), this qualitative descriptive study identifies a critical flaw: a participation gap. Findings reveal that minimal community involvement in the planning and monitoring stages has led to a misalignment between the documented plans and the community's actual needs and aspirations. Consequently, the resulting infrastructure projects risk being underutilized or unsustainable. This study concludes that the existing planning model is procedurally correct but substantively deficient. It proposes a shift towards a more participatory and inclusive planning model that actively integrates community voice as a fundamental component, thereby ensuring that village infrastructure development is not only accountable but also socially sustainable and responsive to local interests.